Pengaruh Kesiapan Organisasi dan Kompetensi Auditor terhadap Keamanan Data Audit pada PT. Agrobisnis Banten Mandiri (Perseroda) Kota Serang - A Deni Iskandarsyah; Fitriana Fitriana; Zaenal Aripin (AKUA: Jurnal Akuntansi dan Keuangan, 2026)
Digital transformation in public sector auditing brings significant challenges to data security. In 2024, Indonesia recorded 21.7 million data breach cases, while audits of regional enterprises revealed weaknesses such as cash-based transactions, invalid attendance records, and unsecured digital assets. These conditions highlight the urgent need for organizational readiness and auditor competence in adopting secure audit technologies. This study aims to examine the influence of organizational readiness and auditor competence on audit data security at PT Agrobisnis Banten Mandiri (Perseroda) Kota Serang. A quantitative approach was applied using descriptive and verificative methods. The research involved all 30 staff members as respondents through total sampling, with data collected via questionnaires, interviews, and documentation. Analysis was conducted using multiple regression with SPSS, supported by validity, reliability, and classical assumption tests. Findings reveal that organizational readiness is relatively strong, though limited by infrastructure and digital oversight culture. Auditor competence is moderate, with adequate regulatory understanding but limited mastery of audit technology. Audit data security has not yet fully aligned with ISO 27001 and the Personal Data Protection Law. Verificative analysis shows organizational readiness has a significant effect on audit data security, auditor competence does not, and together both variables exert a significant influence with organizational readiness as the dominant factor. These results emphasize the importance of strengthening organizational structures to support secure digital audit transformation in regional enterprises.